When timing is key: How autocratic and democratic leadership relate to follower trust in emergency contexts - Rosing, Florian; Boer, Diana; Buengeler, Claudia (Frontiers in Psychology, 2022)
In an emergency team context, leaders’ ability to develop others’ trust in them is a critical aspect of leadership effectiveness. By integrating functional leadership and team process theories, we argue that both democratic and autocratic leadership can create follower trust depending on the performance phase in which the action team is. We argue that action and transition phases produce different task demands for leadership behavior to enhance follower trust, and different leader attributes (marked as leader benevolence and leader ability) mediate these effects. The results of a scenario experiment (N = 125) and field survey (N = 165) among firefighters revealed that autocratic rather than democratic leadership elevates follower trust in the leader during the action phase by increasing perceived leader ability. In contrast, democratic rather than autocratic leadership enhances follower trust in the leader during the transition phase by elevating perceived leader benevolence. Taken together, these findings highlight the importance of follower perception of leader attributes in emergencies and demonstrate the value of mixing autocratic and democratic leadership behaviors across different team performance phases to build follower trust.